1996
DOI: 10.1161/01.hyp.27.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin Prevents Proteinuria and Glomerular Loss of Heparan Sulfate in Diabetic Rats

Abstract: We examined whether blood pressure reduction or good glycemic control equally lower albuminuria by preventing glomerular loss of heparan sulfate and progression of glomerulosclerosis in streptozotocin-induced diabetic rats. We used doxazosin, and alpha 1-adrenergic blocker, to lower systemic blood pressure, and good glycemic control was achieved by insulin treatment. Rats were killed after 20 weeks of treatment. Doxazosin significantly lowered systolic pressure in diabetic rats; however, it had no effect in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…However, combination therapy was superior to either DZN or LIS treatment in preventing glomerular sclerosis in these rats. The observed effect of DZN in lowering blood glucose levels in the present as well as a previous study 17 is an important finding that warrants extensive investigation in diabetic subjects.…”
Section: Reddi Et Al Antihypertensives and Renal Injury In Rats 235supporting
confidence: 84%
See 3 more Smart Citations
“…However, combination therapy was superior to either DZN or LIS treatment in preventing glomerular sclerosis in these rats. The observed effect of DZN in lowering blood glucose levels in the present as well as a previous study 17 is an important finding that warrants extensive investigation in diabetic subjects.…”
Section: Reddi Et Al Antihypertensives and Renal Injury In Rats 235supporting
confidence: 84%
“…17 In addition, DZN was found to lower plasma glucose in these diabetic rats. Drug treatment began 1 week after induction of diabetes; therefore, DZN improved albuminuria and plasma glucose by attenuating the rise in blood pressure.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The decreased nitric oxide synthase (NOS) activity in the kidney of L-NAME-induced hypertensive rats was significantly increased by DOX, and this increase may play a role in the prevention of glomerulosclerosis. Furthermore, Tsai et al (36) reported that DOX inhibits both serum-stimulated and platelet-derived growth factor-induced rat mesangial cell proliferation, and Jyothirmayi et al (37) reported evidence that treatment with DOX may prevent leakage of albumin through the glomerular basement membrane in diabetic rats. Further studies will be needed to confirm the efficacy of combination therapy using an ACEI with an α1-adrenergic antagonist.…”
Section: Discussionmentioning
confidence: 99%